Home Equity Loans (HELs) Utilization among Non-Borrowing Homeowners in the Philippines: A Comprehensive Literature Review - Ramos, John Kenneth (JPAIR Multidisciplinary Research, 2025)
Home equity loans (HELs) provide Filipino homeowners a financial instrument to leverage the accrued value of their properties for diverse needs such as home improvements, education, medical emergencies, or debt consolidation. Despite the evident benefits and relatively favorable terms compared to unsecured loans, many eligible homeowners in the Philippines remain non-borrowers. This phenomenon arises primarily from limited awareness, negative perceptions shaped by cultural and social factors, and structural barriers embedded within the financial and regulatory systems. This comprehensive literature review examines the utilization of home equity loans (HELs) among non-borrowing homeowners in the Philippines. Despite the growing availability of HEL products from government agencies and private banks, many eligible homeowners do not leverage their home equity for financial needs. This study synthesizes findings from recent online sources to examine factors influencing HEL awareness, borrower behavior, product features, structural barriers, and regulatory frameworks. Results indicate that limited financial literacy, documentation challenges, appraisal biases, and risk perceptions significantly constrain HEL uptake. Government initiatives, digital innovations, and financial education programs are pivotal in expanding equitable access. The review concludes with recommendations to enhance HEL utilization and promote inclusive housing finance in the Philippines.
Keywords: Economics; Housing Finance; Financial Literacy; Behavioral Economics; Literature Review; Manila, Philippines